Terrorism and the UN : before and after September 11 - Boulden, Jane, 1962-; Weiss, Thomas G. (Thomas George), 1946- (Indiana University Press, 2004)
Analyses how the UN's role in dealing with terrorism has been shaped over the years by the international system, and how events such as September 11 and the American intervention in Iraq have reoriented its approach to terrorism.